2009
DOI: 10.1007/s10162-009-0176-9
|View full text |Cite
|
Sign up to set email alerts
|

Otoacoustic Emission Theories and Behavioral Estimates of Human Basilar Membrane Motion Are Mutually Consistent

Abstract: When two pure tones (or primaries) of slightly different frequencies (f 1 and f 2 ) are presented to the ear, new frequency components are generated by nonlinear interaction of the primaries within the cochlea. These new components can be recorded in the ear canal as otoacoustic emissions (OAE). The level of the 2f 1 −f 2 OAE component is known as the distortion product otoacoustic emission (DPOAE) and is regarded as an indicator of the physiological state of the cochlea. The current view is that maximal level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The relationship between cochlear compression and MR for speech and pure tones was explored here by estimating cochlear compression for frequencies across the speech bandwidth (500, 1500, and 4000 Hz) using the TMC technique . A recent study has shown that compression estimates using distortion product otoacoustic emissions and TMCs were in good agreement, suggesting that both may be effective at measuring the non-linear functioning of the human cochlea (Lopez-Poveda and Johannesen, 2009). Because hearing loss can vary across frequency, it is important to have a means of estimating compression for several frequencies across the range important for speech.…”
Section: Experiments 3: Estimating Compression and Temporal Resolumentioning
confidence: 99%
“…The relationship between cochlear compression and MR for speech and pure tones was explored here by estimating cochlear compression for frequencies across the speech bandwidth (500, 1500, and 4000 Hz) using the TMC technique . A recent study has shown that compression estimates using distortion product otoacoustic emissions and TMCs were in good agreement, suggesting that both may be effective at measuring the non-linear functioning of the human cochlea (Lopez-Poveda and Johannesen, 2009). Because hearing loss can vary across frequency, it is important to have a means of estimating compression for several frequencies across the range important for speech.…”
Section: Experiments 3: Estimating Compression and Temporal Resolumentioning
confidence: 99%
“…When individually optimal L 1 values were not found, we used the primary level rule of Neely, Johnson, and Gorga (2005) because it has been independently confirmed that this is the most appropriate rule to maximize DPOAE levels on average (cf. Figure 7 in Lopez-Poveda & Johannesen, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…In other words, Lopez-Poveda and Alves-Pinto were suggesting that the absence of DPOAEs in the subjects used by Stainsby and Moore could be more apparent than real due to their using insufficiently sensitive DPOAE techniques. Indeed, Stainsby and Moore used primary tones with a single level of 70 dB SPL each even though DPOAEs depend strongly on the levels of the primary tones (e.g., Figure 7 in Lopez-Poveda & Johannesen, 2009 ), particularly at low frequencies ( Figures 1 and 2 in Johannesen & Lopez-Poveda, 2010 ). Therefore, it is conceivable that DPOAEs may have appeared as absent to Stainsby and Moore but might have been present if they had used different primary levels.…”
Section: Introductionmentioning
confidence: 99%
“…The amplitude is much larger than that of other distortion products, and its existence requires a frequency-selective compressive nonlinearity in basilar membrane mechanics in the region where the primaries overlap. [5,6] This nonlinearity is mainly due to the motility of outer hair cells. [7] These cells are sensitive to noise [8,9] and ototoxic agents.…”
Section: Introductionmentioning
confidence: 99%